Imidazole–Nitrile or Imidazole–Isonitrile CC Coupling on Rhenium Tricarbonyl Complexes. Issue 39 (3rd September 2013) - Viguri, Maialen Espinal; Huertos, Miguel A.; Pérez, Julio; Riera, Lucía
<x xml:space="preserve">Abstract</x> Ligand activation: Deprotonation of the nitrile or isonitrile complexes [Re(CO)3(N‐RIm)2(L)]+ (N‐RIm=N‐alkylimidazole; L=NCtBu, CNtBu) selectively afforded alkylidenamido or iminoacyl derivatives, respectively, in which CC coupling has occurred. Protonation of the latter complex leads to aminocarbene products.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>